Observation of pH Value in Electrokinetic Remediation using various electrolyte (MgSO4, KH2PO4 and Na(NO3)) for Barren Acidic Soil at Ayer Hitam, Johor, Malaysia. Issue 1 (July 2016) - Norashira, J; Zaidi, E; Aziman, M; Azhar, A T Saiful
Abstract: Barren acidic soil collected at Ayer Hitam, Johor Malaysia was recorded at pH value of 2.36 with relative humidity of 86%. This pH value is not suitable for the growth of any plants especially for the soil stabilization purposes. Gradation weathering within the range of 4 to 6 indicates an incomplete/partial weathering process. The soil grade in this range is known as a black shale mudstone. Beside, this also influences to a factor of the high surface water runoff at this particular soil species. As the acidic pH become a major problem for soil fertilizing hence an appropriate technique was implemented known as using 'Electrokinetic Remediation', EKR. This technique has a great potential in changing the soil pH value from acidic to less acidic and also kept maintain the pH at the saturated rate of electrochemical process. This research study presents the monitoring data of pH value due to the effect of various electrolyte consist of 0.5M of MgSO4, KH2 PO4, and Na(NO3 ). Here, the distilled water (DW) was used as reference solution. The electric field was provided by dipping two pieces of identical rectangular aluminum foil as anode and cathode. The EKR was conducted under a constant voltage gradient of 50 V/m across the sample bulk at 0.14 m length measured between both electrodes. The data collection was conducted during the total period of 7 days surveillance. The variation of pH values at the remediation area between anode and cathode for various type of electrolyte indicates that there are a significant saturated value as it reaches 7 days of treatment. During the analysis, it is found that the highest pH value at the remediation area after 7 days treatment using Na(NO3 ), KH2 PO4 and MgSO4 was 3.93, 3.33 and 3.39 respectively. Hence from the last stage of pH value observation, it can be conclude that the best electrolyte for barren soil treatment is Na(NO3 ) whereby it contribute to highest pH value and turn the soil to be less acidic.